HUBUNGAN KUALIFIKASI PETUGAS FILING DENGAN KETEPATAN PENYIMPANAN DOKUMEN REKAM MEDIS DI UPTD BKIM - Alfita Dewi; Ilma Nuria Sulrieni; Ropendi Pardede; Maria Ulfa (Politeknik Negeri Jember, 2023)
Completeness, accuracy, data quality, and timeliness in data collection and arrangement have become essential aspects related to the data processing process in medical records. This study aimed to determine the relationship between the qualifications of Filing officers and the accuracy of medical record storage at the West Sumatra Regional Technical Service Unit of the Eye Health Center. The research was conducted in a quantitative analytical nature with a cross-sectional design. The population included all Medical Record officers and service providers at the West Sumatra Regional Technical Service Unit of the Eye Health Center, totaling 46 people, and the entire population was used as the sample. The research was conducted from January to March 2022. Based on the research results, it was found that 67.4% of the respondents had a high level of education, 58.7% had attended training on medical record storage, 58.7% had been working as medical record storage officers for a long time, and 52.2% were not accurate in storing medical records. The conclusion of the research indicates that more than half of the respondents had a high level of education and training, but they were not accurate in storing medical records. There was no strong correlation between the length of employment and the accuracy of medical record storage (p = 0.341). Researchers suggest the need for long-term planning for the success of the West Sumatra Regional Technical Service Unit of the Eye Health Center in improving the quality of medical record storage accuracy, especially in terms of human resources, such as recruiting personnel with a background in medical records and participating in various medical record training programs. By doing so, the management can minimize inaccuracies in medical record storage.